The value of diastolic speckle-tracking parameters in predicting outcome after surgical ventricular restoration. (4th February 2022) - Nemchyna, O; Solowjowa, N; Dandel, M; Hrytsyna, Y; Stein, J; Knierim, J; Schoenrath, F; Falk, V; Knosalla, C
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): DZHK (German Centre for Cardiovascular Research) BMBF (German Ministry of Education and Research) Background. Parameters of speckle-tracking echocardiography (STE) are incorporated into the integrative assessment of left ventricular (LV) diastolic function 1. In this study we aimed to evaluate both established and novel STE parameters of LV diastolic function and their prognostic role in patients with LV anteroapical aneurysm planned for surgical ventricular restoration (SVR). Methods. We retrospectively examined data of 137 patients (60 ± 11 years, 25% women) with anteroapical LV aneurysm who underwent SVR and for whom preoperative echocardiography was available and feasible for STE and for conventional assessment of LV diastolic function by transmitral flow. STE parameters evaluated were: left atrial reservoir strain (LAS), early and late global diastolic strain rate (GLSRe and GLSRa), ratio of early-to-late diastolic strain rate (GLSRe/GLSRa), and ratio of early diastolic transmitral flow velocity (E) to GLSRe and to GLSRa. In 24 patients we evaluated an association of diastolic echocardiographic parameters with mean pulmonary artery pressure (PAPm) and mean pulmonary capillary wedge pressure (PCWPm) obtained invasively within 6 days of echocardiography. Preoperative echocardiographic parameters were assessed in whole cohort of patients for the association with an outcome, defined as all-cause mortality, LV assist device implantation, or heart transplantation. Results. During a median follow-up of 4.7 years (IQR: 1.4-8.1 years) events occurred in 59 patients. GLSRa, E/GLSRa and LAS demonstrated significant correlation with PAPm and PCWPm (Table 1). GLSRa with optimal cut-off value of ≤ 0.41 s-1 was able to detect PAPm >30 mmHg with sensitivity of 0.8 and specificity of 0.8 (AUC 0.85; 95% CI 0.68-1.0; p = 0.008). E/GLSRa ≥1.24 m was able to detect PAPm >30 mmHg with sensitivity of 1.0 and specificity of 0.8 (AUC 0.87; 95%CI 0.7-1.0; p = 0.005). There was significant difference in event-free survival between groups stratified by cut-offs for GLSRa (Fig. 1A) and E/GLSRa (Fig. 1B). After adjustment for important clinical (age, sex, plasma creatinine, atrial fibrillation) and echocardiographic parameters (fractional shortening and LV end-systolic volume index) GLSRa and E/GLSRa remained an independent predictors of events (HR 0.16; 95% CI: 0.03-0.86; p = 0.032 and HR 1.22; 95% CI: 1.03-1.43; p = 0.018) and demonstrated higher prognostic value compared to LAS, other STE parameters and conventional parameters of LV diastolic function. Conclusion. Late diastolic longitudinal strain rate and ratio of early diastolic transmitral flow velocity to late diastolic longitudinal strain rate demonstrated association with hemodynamic parameters in patients with LV anteropaical aneurysm and might be used for the evaluation of LV diastolic function. These parameters showed prognostic value for patients underwent SVR and could be implemented for preoperative evaluation of these patients.